(untitled) (Bangladesh Journal of Medical Education, 2019)
Background: Goal-Oriented Learning (GOL) pedagogy might increase dental students’ skill to achieve desired public health goal. Purpose: The objective of this study is to assess the effectiveness of GOL system in terms of increasing knowledge retention as method of curriculum delivery in comparison to traditional lecture method and to explore the perceptions and experiences of students and tutors in regards to GOL system. Method: The study was conducted among all the 2nd year BDS, Sapporo Dental College using Quasi-Experimental design. Intervention and control group were taught using GOL and lecture based method, respectively. SAQ type questions were used to assess the level of knowledge before and after intervention in both groups. Students and tutors perceptions and experiences were evaluated using modified course experience questionnaire and tutor response questionnaire. Result: Level of good score and mean knowledge score differences between pre-test and post-test were more observed in GOL group. These differences found are statistically significant. Though most of the students of GOL system perceived that it contributes in developing their generic skill like improving problem solving, analytic and expression skill, majority of them reported that workload was heavy on them. Most of students were satisfied relating to tutor role, facilities available and evaluation system in GOL group. Overall satisfactions were superior in GOL groups in comparison to lecture group among both students and tutors. Conclusion: The study showed that GOL system significantly improves knowledge retention in comparison to traditional lecture system. Moreover, majority of students and tutors gave more positive feedback regarding GOL experience and consider it superior than lecture-based system. Bangladesh Journal of Medical Education Vol.10(1) 2019: 25-29